Is Plea Bargaining in the “Shadow of the Trial” a Mirage? - Bushway, Shawn (Journal of quantitative criminology, 2012)
It has been well established that a “plea discount” or “trial penalty” exists, such that defendants who plead guilty receive significant sentencing discounts relative to what they would receive if convicted at trial. Theorists argue that the exact value of this plea discount is determined by bargaining “in the shadow of a trial,” meaning that plea decision-making is premised on the perceived probable outcome of a trial. In trials, the strength of the evidence against defendants greatly impacts the probability of conviction. In the present study, we estimate the probability of conviction at the individual level for those who pled guilty. We find that, contrary to the shadow of the trial model, evidentiary factors either do not impact or negatively impact the probability of conviction, which stands in stark contrast to the impact evidence has at trials. These findings suggest that plea bargain decision-making may not occur in the shadow of the trial.